Spotted Seals, Phoca largha, in Alaska - Rugh, David J.; Shelden, Kim E. W.; Withrow, David E. (1997)
The worldwide literature on management of spotted seals, Phoca largha, was reviewed and updated, and aerial surveys weref lown in 1992 and 1993 to determine the species' distribution and abundance in U.S. waters. In April, spotted seals were found only in the Bering Sea ice front. In June, they were seen along deteriorating ice floes and fast ice in Norton Sound. Surveys along most of Alaska's western coast in August and September found over 2,500 spotted seals in Kuskokwim Bay and concentrations of 100-400 seals around Nunivak Island, Scammon Bay, Golovnin Bay/Norton Sound, Cape Espenberg/Kotzebue Sound, and Kasegaluk Lagoon. All of these sites have been used by spotted seals in the past. The sum of the highest counts, irrespective of year, was 3,570 seals (CV =0.06). This is not an abundance estimate for all spotted seals in the Bering Sea, because it does not account for animals in the water, and we did not survey the Asian coast and some islands. Also, spotted seals and harbor seals, Phoca vitulina, are too similar in appearance to be identified accurately from the air, so our results probably include a mix of these species where their ranges overlap.